Effect of surgery-induced acute muscle wasting on postoperative outcomes and quality of life - Huang, Dong-Dong; Ji, Yan-Bin; Zhou, Dong-Lei; Li, Bo; Wang, Su-Lin; Chen, Xiao-Lei; Yu, Zhen; Zhuang, Cheng-Le (The Journal of surgical research, 2017)
Gastrectomy results in a significant loss of body composition in the long term, but the acute skeletal muscle wasting after gastrectomy has been rarely investigated. Moreover, the association between postoperative muscle wasting and quality of life (QOL) has never been reported. In the present study, we aimed to investigate the risk factors for acute muscle wasting after gastric cancer surgery and its effect on QOL and short-term postoperative outcomes. We conducted a prospective study of patients who underwent curative gastrectomy for gastric cancer between June 2015 and December 2015. Skeletal muscle mass was measured by computed tomography within 1 month before and 1 week after surgery. QOL was assessed 1, 3, and 6 months postoperatively. Univariate and multivariate analyses were performed to identify the risk factors for clinically relevant muscle wasting (muscle wasting ≥10%). A total of 110 patients were included, in which 35 patients had muscle wasting ≥10% within 1 week after surgery. Age ≥65 years and diabetes were independent risk factors for muscle wasting ≥10%. Patients with muscle wasting ≥10% had a poorer QOL in terms of fatigue and physical functioning at 1 and 3 months postoperatively, as well as a higher incidence of postoperative complications, a higher incidence of handgrip strength reduction ≥10%, longer hospital stays, and higher costs. Age ≥65 years and diabetes were independently associated with clinically relevant muscle wasting within 1 week after gastric cancer surgery. Clinically relevant muscle wasting was associated with a poorer QOL and short-term outcomes after surgery.